2009
DOI: 10.1890/07-1880.1
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning beta diversity in a subtropical broad‐leaved forest of China

Abstract: Abstract. The classical environmental control model assumes that species distribution is determined by the spatial variation of underlying habitat conditions. This niche-based model has recently been challenged by the neutral theory of biodiversity which assumes that ecological drift is a key process regulating species coexistence. Understanding the mechanisms that maintain biodiversity in communities critically depends on our ability to decompose the variation of diversity into the contributions of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
696
9
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(768 citation statements)
references
References 37 publications
32
696
9
10
Order By: Relevance
“…In smaller spatial scales, a spatially structured environment may favor limitations in the dispersion of species, and neighboring environments tend to be similar (Karst et al 2005). This fact is very clear in the studied hillside, because the strongest predictive variables (elevation and slope) were spatially structured along the gradient, as also observed by Legendre et al (2009).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In smaller spatial scales, a spatially structured environment may favor limitations in the dispersion of species, and neighboring environments tend to be similar (Karst et al 2005). This fact is very clear in the studied hillside, because the strongest predictive variables (elevation and slope) were spatially structured along the gradient, as also observed by Legendre et al (2009).…”
Section: Discussionmentioning
confidence: 53%
“…A fraction related to spatially structured environment (R 2 = 8%) may also be used to justify the distance-decay floristic similarity (DinizFilho et al 2012). Legendre et al (2009) andDiniz-Filho et al (2012) suggest that a spatially structured environment has an influence on the spatial distribution of species, because as distance between environments increases, the higher their difference in terms of species composition. In smaller spatial scales, a spatially structured environment may favor limitations in the dispersion of species, and neighboring environments tend to be similar (Karst et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that both groups of processes jointly regulate ecological communities (Chave, 2004) with varying relative effects depending on geographic scales and strength of environmental gradients (see Hanson et al, 2012) and type of organism (body size, dispersal mode, see Soininen et al, 2007). At smaller scales, habitat heterogeneity declines, which generally results in lower habitat preference and therefore greater importance of stochastic processes over deterministic factors (Legendre et al, 2009;Chase, 2014). However, the evolutionary and ecological factors that influence dispersal of organisms may also diminish with decreasing geographic scale (Warren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several studies have demonstrated a host of different factors that may influence variation of species composition through space: (1) spatial and environmental gradients (e.g. Clark et al, 1999;Nekola & White, 1999;Oliveira-Filho & Fontes, 2000;Carneiro & Valeriano, 2003;Steinitz et al, 2006Steinitz et al, , 2007bLegendre et al, 2009); (2) differences in the physiology, in the degree of biological interactions and in the dispersal ability of the species (Nekola & White, 1999;Tuomisto et al, 2003;Gilbert & Lechowicz, 2004); (3) barriers imposed by the configuration of the landscape and the influence of weather on species' dispersion (Nekola & White, 1999;Hubbel, 2001); (4) stochastic processes generated randomly and independently of environmental dissimilarities (Neutral Theory sensu Hubbel, 2001;Soininen et al, 2007b;Steinbauer et al, 2012); (5) species' tolerance to fragmentation (Arroyo-Rodríguez et al, 2013); (6) spatial scale (extension, resolution; Nekola & White, 1999;Steinitz et al, 2006;Soininen et al, 2007b;Arroyo-Rodríguez et al, 2013). Therefore, more accurate analysis involving other variables could yield further explanations regarding the spatial distribution observed in this study.…”
Section: Discussionmentioning
confidence: 99%